2013
DOI: 10.12659/msmbr.889350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preparation techniques on root canal shaping assessed by micro-computed tomography

Abstract: BackgroundRoot canal shaping without any procedural error is of the utmost preference. Therefore, the purpose of this study was to use micro-computed tomography to evaluate and compare the root canal shaping efficacy of ProTaper rotary files and standard stainless steel K-files.Material/MethodsSixty extracted upper second premolars were selected and were divided into 2 groups of 30. Before preparation, all samples were scanned by micro-CT. Then, 30 teeth were prepared with stainless steel files and the remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…This result differs from previous studies that indicate that the apical segment usually has more canal transportation toward the outside of the curve. 19,22,25 As in the present study, an average deviation from the direction of the different thirds was used, and hence our results probably reflect the higher incidence of deviation inside of the curve that occurs in the cervical and middle segments, as previously reported by Stavileci et al 9 An important difference between the NiTi systems used in the present study is related to the number of the files used. ProTaper and Twisted File systems use a small number of files in an attempt to simplify the root canal instrumentation, whereas Hero and Liberator systems allow the use of a larger number of instruments.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…This result differs from previous studies that indicate that the apical segment usually has more canal transportation toward the outside of the curve. 19,22,25 As in the present study, an average deviation from the direction of the different thirds was used, and hence our results probably reflect the higher incidence of deviation inside of the curve that occurs in the cervical and middle segments, as previously reported by Stavileci et al 9 An important difference between the NiTi systems used in the present study is related to the number of the files used. ProTaper and Twisted File systems use a small number of files in an attempt to simplify the root canal instrumentation, whereas Hero and Liberator systems allow the use of a larger number of instruments.…”
Section: Discussionsupporting
confidence: 65%
“…9,25 In the present study, we observed a greater incidence of distal deviations (inside of the curve) on all systems used. This result differs from previous studies that indicate that the apical segment usually has more canal transportation toward the outside of the curve.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Glosson et al [18], Gambill et al [11], Short et al [19], Elliot et al [20], and Schäfer and Florek [21] revealed a better centering ability in the preparation using NiTi instruments than using stainless steel instruments. According to Stavileci et al [22], the centralization capacity of NiTi instruments is in part determined by their characteristic flexibility.…”
Section: Resultsmentioning
confidence: 99%